Die Modernisierung politischer Systeme Staat. Parteien. Öffentlichkeit - Wimmer, Hannes (2000)
Part one of the book discusses political systems of Developing Countries. It suggests that the concept of neopatrimonialism is becoming more and more important. Neopatrimonial systems are characterized by three components: Personal rule, political clientelism and endemic corruption. The neopatrimonial state is essentially a weak state, where the production of public goods is very low and the road to the failure of the state open. For the transformation or improvement of a neopatrimonial system a developmental state is necessary. Part two tries to give a theory of the state. The state is understood as a set of complex institutions. Historical institutionalism seems therefore to be the correct approach. Four institutional complexes are needed for consolidated modern statehood: The military for the security of the state - the military revolution can be regarded as the most important factor in explaining the origin of the state. Territorial segmentation is at the same time the building principle for the international political system. As the professionalism of the military increases, a new institutional complex becomes necessary for the security of the citizens: the police, and the police is the institution for the monopoly of legitimate violence. The second institutional complex is taxation and the ordering of state finances (the budget). Taxes are historically a consequence of standing armies. Today taxation is an important dimension of state capabilities. The third complex is the bureaucracy - necessary for the production of decisions based on general rules. An effective bureaucracy is a precondition for the development of the welfare state. Corruption its main problem. The forth complex is placed at the top of the state - governing all the other institutions. It is essentially the government in combination with the parliament as a law-making institution. Part three tries to explain the process of democratization. Democracy needs three subsystems: the public sphere as the interaction of mass media and discourses of the citizens. A party system, where the parties are based on political ideologies. And a parliament, as the center of a representative government. Responsiveness can be explained as a consequence of general free elections.